Practical statistics for geographers and earth scientists - Walford, Nigel (Hoboken Jon wiley & Sons Ltd., 2025)
Statistical analysis is a requirement on geography and earth science degree courses, usually taught as a module in year 2 or 3. There is a need for a textbook which includes examples that are relevant to earth scientists and geographers, and which introduces the subject in language and terminology which is accessible to undergraduate students in these subjects.